The Concept Of Thinking Of Islamic Religious Education By Muhammad Abduh - Fatimah Az-Zahra; Nuranisa Nuranisa; Siti Nurhasanah (Yayasan Rahmat Islamiyah, 2021)
Muhammad Abduh was one of the figures of Islamic reform in the 19th century who had very wise ideas in Islamic reform. Because Muhammad Abduh could revive the enthusiasm of the people to continue to advance and work in the field of science. Muhammad Abduh started his improvement from the field of education and made education the main means of saving Egyptian society. Then make the improvement of education as the foundation for creating a pious and pious generation. The education carried out by Muhammad Abduh aims to educate the minds and souls of generations and strive to continue to develop them so that goals for happiness in the world and the hereafter can be achieved. The connection with the curriculum is that Muhammad Abduh wanted an integral Islamic education curriculum at every level of education with the aim of education.Keywords: Education, Muhammad Abduh